2008
DOI: 10.1161/circulationaha.108.776757
|View full text |Cite|
|
Sign up to set email alerts
|

Dose Effect of Clopidogrel Reloading in Patients Already on 75-mg Maintenance Dose

Abstract: Background-Clopidogrel loading has mostly been studied in clopidogrel-naïve patients. Whether clopidogrel-treated patients readmitted for an acute coronary syndrome or percutaneous coronary intervention can benefit from a new load of clopidogrel and at what dose remain unknown. Our aim was to evaluate the impact of 3 different strategies of administration of a loading dose of 900 mg clopidogrel in patients already treated with a maintenance dose of 75 mg clopidogrel for at least 7 days on residual platelet agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(15 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…5 Aspirin and clopidogrel pharmacodynamic responses were evaluated with light transmission aggregometry (arachidonic acid 1.25 mol/L and ADP 20 mol/L; results expressed in percent residual platelet aggregation [RPA]) and with the VerifyNow assay (results expressed in aspirin reaction units with the aspirin cartridge and P2Y 12 reaction units and percent inhibition with the P2Y 12 cartridge). Aspirin resistance was defined either by an RPA Ͼ20% with arachidonic acid or by an aspirin reaction unit Ն550.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…5 Aspirin and clopidogrel pharmacodynamic responses were evaluated with light transmission aggregometry (arachidonic acid 1.25 mol/L and ADP 20 mol/L; results expressed in percent residual platelet aggregation [RPA]) and with the VerifyNow assay (results expressed in aspirin reaction units with the aspirin cartridge and P2Y 12 reaction units and percent inhibition with the P2Y 12 cartridge). Aspirin resistance was defined either by an RPA Ͼ20% with arachidonic acid or by an aspirin reaction unit Ն550.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…The RELOAD and ARMYDA-4 RELOAD trials attempted to address the question of whether an additional loading dose of clopidogrel was required prior to PCI in stable and ACS patients who were already receiving chronic clopidogrel therapy (51)(52). The trials found that although clopidogrel reloading produced significantly greater levels of platelet inhibition, there was no difference in the primary endpoint of MACE.…”
Section: Clopidogrelmentioning
confidence: 99%
“…Collet and colleagues report the findings of a randomized clinical trial that evaluated residual platelet aggregation (RPA) after administration of 900 mg of clopidogrel provided in 3 dosing strategies. 12 Clopidogrel reloading was accomplished by either a single 900-mg dose followed 4 hours later with a placebo dose, or by split dosing with an initial bolus of 600 or 300 mg, followed 4 hours later by a second dose of 300 or 600 mg, respectively. Each patient had been treated with clopidogrel long term, the majority for a duration of Ͼ30 days.…”
Section: Article P 1225mentioning
confidence: 99%
“…12 We can achieve a greater level of inhibition of platelet aggregation by reloading patients on long-term clopidogrel therapy with a 600-to 900-mg LD. In low-risk patients or those known to have adequate IPA on long-term therapy, we can probably relax and not become too concerned about additional clopidogrel reloading, although it is unlikely to be harmful.…”
Section: Article P 1225mentioning
confidence: 99%